Effects of metformin in obesity treatment in different populations: a meta-analysis. (May 2020) - Pu, Ruiyang; Shi, Dian; Gan, Ting; Ren, Xiaoyu; Ba, Yupei; Huo, Yanbei; Bai, Yana; Zheng, Tongzhang; Cheng, Ning
Objective: Some studies have shown that metformin can reduce body weight. However, metformin has not been officially approved as a medicine for weight loss because its effect on different populations remains inconsistent. This meta-analysis aimed to summarize the weight loss effect of metformin quantitatively. Method: The randomized controlled and high-quality case-control trials of metformin monotherapy in obesity treatment were eligible. Baseline body mass index (BMI) was chosen as a self-control to compare the changes in BMI of different populations before and after treatment. All changes were calculated as differences between the final and initial BMI values (with negative values indicating a decrease). Results were presented as weighted mean difference (WMD) with a 95% confidence interval (CI 95%). Subgroup analysis was performed based on baseline BMI, age, daily dose, and duration of medication. Results: A total of 21 trials ( n  = 1004) were included, and the meta-analysis of metformin treatment in different populations showed that metformin has a modest reduction in the BMI of included participants (WMD −0.98; 95% CI, −1.25 to −0.72), and the reduction of BMI was most significant in the simple obesity population (WMD −1.31; 95% CI, −2.07 to −0.54). The subgroup analysis showed that metformin treatment significantly reduced BMI in obesity patients with a BMI >35kg/m 2 (WMD −1.12; 95% CI, −1.84 to −0.39) compared with before treatment. BMI in the high dose group decreased by 1.01 units (WMD−1.01; 95% CI, −1.29 to −0.73) and BMI did not continue to decrease significantly after treatment of more than 6 months. Conclusion: Patients treated with metformin experienced about a one-unit reduction in BMI at the end of treatment. But whether this decreased value produced enough weight loss (5% of baseline body weight) to qualify as a "weight loss drug" as current guidelines require, requires larger specific randomized control trials.